PROGRAM KELUARGA HARAPAN (PKH): MEMOTONG MATA RANTAI KEMISKINAN ANAK BANGSA - Suharto, Edi; Thamrin, Djuni (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2012)
In addition to describing the progress and challenges faced byThe Family HopeProgram (PKH), this paper also aims to explain the theoretical basis of social protection programs that under lie PKH. This paper was based ona series ofdirect observation combined with a desk reviewof the CCT implementation unit level and regional centers as well as afocus group discussion with partners/facilitator in the field, experts of PKH, area coordinator, regional coordinator and RTSM beneficiaries. This study showed that the CCT provide significants up port for Very Poor Households, “Rumah Tangga Sangat Miskin”(RTSM) in order not to”produce” the next generation who were malnourished and uneducated. The program alsogave an opportunity for scholars working in the area to engage in these activities. Until 2012, PKH absorbed nearly 10,000 young workforceas mentors, operators, area coordinators from higher education graduates.